Innovative Approach to Training Sustainable Engineers - Atayeva, Shemshat; Garlyyeva, Chynar; Orazov, Yslam (Journal of Sustainability Perspectives, 2023)
Oguz han Engineering and Technology University of Turkmenistan is a higher education institution, which specializes in training engineers with innovative views. Training of future professionals that “Engineer a Sustainable World” requires not only new competencies, including creative learning and thinking, complex problem-solving interdisciplinary and international cooperation, and a code of ethics, but also challenges a change in engineering education itself. In our approach, we suggest innovative ways to develop a deeper working knowledge of technical fundamentals while simultaneously learning personal and interpersonal skills, and product, process, and system building skills. For analysis of interrelated arrangement of modules for effective acquisition of knowledge, a supportive alignment of disciplinary courses was studied and a wide range of skills required in professional areas were mapped throughout the curriculum. Moreover, we created a new learning context that provides an opportunity to implement both theoretical and practical knowledge to conceive, design, implement and operate real-world systems and products. In this approach, we developed integrated methods of gaining active learning experience that forms a basis for carrying out challenging capstone projects. As a result, our innovative approach that focuses on modification of education and research improves all aspects of comprehensive training of sustainable engineers.